Give an equation for c not involving a.?

Combine c=4a-3 and 2b=3a-8

8 Answers

Relevance
  • 1 month ago

    c=4a-3--------(1)

    2b=3a-8--------(2)

    3(1)-4(2)

    =>

    3c-8b=-9+32

    =>

    3c=23+8b

    =>

    c=(23+8b)/3

  • Philip
    Lv 6
    1 month ago

    c=4a-3...(1), 2b=3a-8...(2).;

    (2)---> a = (1/3)2(b+4) = (2/3)(b+4).;

    Then (1)---> c = 4[(2/3)(b+4)] -3 = (8/3)b +(32/3) -(96/3) = (8/3)b -(64/3) = (8/3)(b-8);

    ie., c = (8/3)(b-8).

  • 1 month ago

    An equation for c not involving a.

    Combine c = 4a - 3 and 2b = 3a - 8

    a = (c + 3)/4

  • Ian H
    Lv 7
    1 month ago

    12a = 3(c + 3) = 4(2b + 8)

    3c = 8b + 23

  • What do you think of the answers? You can sign in to give your opinion on the answer.
  • Jeremy
    Lv 6
    1 month ago

    1)

    c = 4a - 3 ===> c + 3 = 4a ===> a = (c + 3)/4.

    2) 

    2b = 3a - 8 ===> 2b + 8 = 3a ===> a = (2b + 8)/3.

    3)

    If "a = (c + 3)/4" and "a = (2b + 8)/3", therefore:

    (c + 3)/4 = (2b + 8)/3.

    3 * (c + 3) = 4 * (2b + 8).

    3 * c + 3 * 3 = 4 * 2b + 4 * 8.

    3c + 9 = 8b + 32.

    3c = 8b + 32 - 9.

    3c = 8b + 23.

    c = (8b + 23)/3 <=== ANSWER. 

    Or, alternatively: c = (8/3) * b + 23/3. 

  • 1 month ago

    c = 4a - 3 and 2b = 3a - 8

    The second equation can be re-arranged to make a the subject

    so, 3a = 2b + 8

    Hence, a = (2b + 8)/3

    Putting this into the first equation for a gives:

    c = 4(2b + 8)/3  - 3

    or, c = 8b/3 + 32/3 - 9/3

    so, c = 8b/3 + 23/3

    Then, c = (8b + 23)/3....which gives c in terms of b

    :)>

  • 1 month ago

    given c=4a-3, now 4a=3-c, => a=3-c/4  & similarly a=2b+8/3 , solve them

  • 1 month ago

    If you want to remove the "a", then solve one equation for "a" in terms of the other variable and substitute into the other equation.  This will give you a new equation with two unknowns, "b" and "c".  Then you can solve for c.

    So we have:

    c = 4a - 3 and 2b = 3a - 8

    The first is already c in terms of a, so we want to leave that alone for now.  Solve the other one for a in terms of b:

    2b = 3a - 8

    2b + 8 = 3a

    (2b + 8) / 3 = a

    Now we can substitue that expression for "a" in the other equation:

    c = 4a - 3

    c = 4(2b + 8) / 3 - 3

    Let's distribute the 4 and get a common denominator so we can simplify this:

    c = (8b + 32) / 3 - 9 / 3

    Now we can subtract the numerators:

    c = (8b + 32 - 9) / 3

    and simplify:

    c = (8b + 23) / 3

    or:

    c = (8/3)b + 23/3

    Either gives you c in terms of b.

Still have questions? Get answers by asking now.